Capital structure design of foreign subsidiaries in multinational corporate groups with a German parent company - Andreas Hoffjan; Michael Rosmann (Westfälische Wilhelms-Universität Münster, Lehrstuhl für Betriebswirtschaftslehre, insb. Controlling, 2002)
This essay gives an overview of the special features of funding foreign subsidiaries. The central issue discussed is the possibility of funding by equity capital borrowed capital in the form of loans and trade accounts payable. Various envirenmental settings are introduced which lead to different decisions regarding the capital structure. The observations relate to a subsidiary company that is to be set up a new, where the possibility of design in the capital structure is given and therefore existing financing structures are not considered.
Keywords: 650